2012
DOI: 10.1111/j.1476-5381.2012.01835.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of disodium isostearyl 2‐O‐L‐ascorbyl phosphate, an amphiphilic ascorbic acid derivative, reduces neuropathic hyperalgesia in rats

Abstract: BACKGROUND AND PURPOSECav3.2 T-type calcium channels, targeted by H2S, are involved in neuropathic hyperalgesia in rats and ascorbic acid inhibits Cav3.2 channels. Therefore, we evaluated the effects of intraplantar (i.pl.) administration of ascorbic acid or topical application of disodium isostearyl 2-O-L-ascorbyl phosphate (DI-VCP), a skin-permeable ascorbate derivative on hyperalgesia induced by NaHS, an H2S donor, and on neuropathic hyperalgesia. EXPERIMENTAL APPROACHIn rats mechanical hyperalgesia was evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
(85 reference statements)
0
9
0
Order By: Relevance
“…Strikingly, we have detected significant decrease in levels of ascorbic acid (vitamin C), known to selectively inhibit Ca v 3.2 (see Fig. 1), in the hindpaw tissue of rats with paclitaxelinduced neuropathy (13). We have also shown that intraplantar injection of ascorbic acid or topical application of disodium isostearyl 2-O-l-ascorbyl phosphate (DI-VCP), a skin-permeable ascorbate derivative, abolishes the H 2 S-induced hyperalgesia and paclitaxel-induced neuropathy and also partially inhibits the spinal nerve injury-induced neuropathy (13).…”
Section: Involvement Of T-channels In Neuropathic Painmentioning
confidence: 98%
See 1 more Smart Citation
“…Strikingly, we have detected significant decrease in levels of ascorbic acid (vitamin C), known to selectively inhibit Ca v 3.2 (see Fig. 1), in the hindpaw tissue of rats with paclitaxelinduced neuropathy (13). We have also shown that intraplantar injection of ascorbic acid or topical application of disodium isostearyl 2-O-l-ascorbyl phosphate (DI-VCP), a skin-permeable ascorbate derivative, abolishes the H 2 S-induced hyperalgesia and paclitaxel-induced neuropathy and also partially inhibits the spinal nerve injury-induced neuropathy (13).…”
Section: Involvement Of T-channels In Neuropathic Painmentioning
confidence: 98%
“…1), in the hindpaw tissue of rats with paclitaxelinduced neuropathy (13). We have also shown that intraplantar injection of ascorbic acid or topical application of disodium isostearyl 2-O-l-ascorbyl phosphate (DI-VCP), a skin-permeable ascorbate derivative, abolishes the H 2 S-induced hyperalgesia and paclitaxel-induced neuropathy and also partially inhibits the spinal nerve injury-induced neuropathy (13). These findings are consistent with some clinical evidence for the decreased plasma vitamin C levels in post-herpetic neuralgia patients (33,34) and for the therapeutic value of ascorbic acid in patients with post-herpetic neuralgia (33,35) or with complex regional pain syndrome after wrist fractures (36).…”
Section: Involvement Of T-channels In Neuropathic Painmentioning
confidence: 99%
“…Thus, H191 is an important site for fine tuning of neuronal excitability in cells that express T-channels. However, because highly redox reactive metals such as copper (Cu (50), in an excellent in vivo pain study, have shown that a skin-permeable formulation of ointment containing ascorbic acid applied to peripheral receptive fields of nociceptors suppressed neuropathic hyperalgesia induced by application of NaHS (donor of H 2 S in tissues) or by mechanical injury of the spinal nerve or by systemic administration of the neurotoxic anti-cancer drug paclitaxel. In this study, the analgesic effects of ascorbate were mimicked fully by the T-type channel blocker NNC 55-0396.…”
Section: Molecular Mechanisms Of Modulation Of Ca V 32 T-current By mentioning
confidence: 99%
“…H 2 S targets multiple molecules including ion channels, such as ATP-sensitive K + (K ATP ) channels [5,6], T-type Ca 2+ channels [7][8][9][10], L-type Ca 2+ channels [11,12], transient receptor potential ankyrin-1 [13] and large conductance Ca 2 + -activated K + channels [14]. Among three isoforms of T-type Ca 2+ channels, Ca v 3.2 mediates the facilitation of somatic and visceral pain signals by H 2 S [7,8,15,16], and the increased activity of the H 2 S/Ca v 3.2 pathway is involved in neuropathic pain and in pancreatic and bladder nociception accompanying pancreatitis and cystitis, respectively [17][18][19][20][21]. The enhanced activity of Ca v 3.2 by NaHS, a donor of H 2 S, also causes neuronal differentiation characterized by neurite outgrowth and functional upregulation of high voltage-activated Ca 2+ channels in NG108-15 cells (mouse neuroblastoma  rat glioma hybrid cells) [22][23][24].…”
Section: Introductionmentioning
confidence: 99%